SOSIALISASI PRODUK - PRODUK PASAR MODAL SEBAGAI WADAH INVESTASI BAGI PEREMPUAN - aira, Aras; Nurlita, Anna; Irdayanti, Irdayanti; Nesneri, Yessi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The capital market is one place to make investments, investments can be made by anyone, including women, women is very important to know this investment, in order to be able to do good financial management, but the number of women who invest in the capital markets is still small, this socialization is aimed at increasing women's knowledge about capital market products, socialisation is a method done to increase women' s knowledge of capital market product. At this PKM participants are female housekeepers and female workers at Tuah Madani district, the number of participants 22 people carried out on Wednesday, July 19, 2023. After conducting socialization, the servant team concluded that there had been an improvement in the knowledge of the capital market in particular about the products of capital markets in PKM participants from the comparison of Prestest and Postest submitted to the dedication participants..